2014
DOI: 10.1111/bph.12685
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of antagonists with subtypes of inositol 1,4,5‐trisphosphate (IP3) receptor

Abstract: Background and PurposeInositol 1,4,5-trisphosphate receptors (IP3Rs) are intracellular Ca2+ channels. Interactions of the commonly used antagonists of IP3Rs with IP3R subtypes are poorly understood.Experimental ApproachIP3-evoked Ca2+ release from permeabilized DT40 cells stably expressing single subtypes of mammalian IP3R was measured using a luminal Ca2+ indicator. The effects of commonly used antagonists on IP3-evoked Ca2+ release and 3H-IP3 binding were characterized.Key ResultsFunctional analyses showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
112
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(115 citation statements)
references
References 81 publications
1
112
1
Order By: Relevance
“…IP3-sensitive phenylephrine-induced phasic contractions do not involve extracellular Ca 2 þ influx α 1 -Adrenoceptor stimulation of mouse aortic segments with phenylephrine in the absence of extracellular Ca 2 þ caused transient isometric contractions, which were inhibited with 2-APB. The IC 50 of 2-APB was below the concentration of 50 mM, which is the highest concentration that avoided inhibition of Ca 2 þ uptake to the SR (SERCA), but caused a sevenfold decrease in IP 3 -sensitivity of the IP 3 receptor (Saleem et al, 2014). Therefore, the phenylephrineinduced phasic contraction in 0Ca is due to Ca 2 þ release through IP 3 receptor activation via IP 3 formation (Manolopoulos et al, 1991;Yamamura et al, 2012).…”
Section: Ca 2 þ Leaks From the Vsmc Sr Are Counteracted By Basal Ca 2mentioning
confidence: 96%
See 1 more Smart Citation
“…IP3-sensitive phenylephrine-induced phasic contractions do not involve extracellular Ca 2 þ influx α 1 -Adrenoceptor stimulation of mouse aortic segments with phenylephrine in the absence of extracellular Ca 2 þ caused transient isometric contractions, which were inhibited with 2-APB. The IC 50 of 2-APB was below the concentration of 50 mM, which is the highest concentration that avoided inhibition of Ca 2 þ uptake to the SR (SERCA), but caused a sevenfold decrease in IP 3 -sensitivity of the IP 3 receptor (Saleem et al, 2014). Therefore, the phenylephrineinduced phasic contraction in 0Ca is due to Ca 2 þ release through IP 3 receptor activation via IP 3 formation (Manolopoulos et al, 1991;Yamamura et al, 2012).…”
Section: Ca 2 þ Leaks From the Vsmc Sr Are Counteracted By Basal Ca 2mentioning
confidence: 96%
“…2), a putative inhibitor of the IP 3 -receptor and the IP 3 -mediated Ca 2 þ release from the SR(Lamont and Wier, 2004;Saleem et al, 2014). 2-APB inhibited the transient contraction with an IC 50 of 327 4 mM (n ¼4,Fig.…”
mentioning
confidence: 93%
“…Moreover, the quality of the antibodies raised against IP 3 R2 was also generally poor. Finally, a recent analysis of classically used IP 3 R inhibitors demonstrated that IP 3 R2 expressed in DT40 triple knockout (DT40 TKO) chicken B lymphocytes was the least sensitive of all the IP 3 R isoforms to heparin, caffeine and 2-aminoethoxydiphenyl borate [44]. This latter observation may explain why pharmacological approaches to discern IP 3 R2 function have been largely unsuccessful.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that additional pathways may have been modified by caffeine such as Ca 2þ and oocyte kinases. High concentrations (>10 mM) of caffeine have antagonistic effects on inositol triphosphate receptors (IP 3 R) [25]. Inositol triphosphate receptors are intracellular Ca 2þ channels located in the endoplasmic reticulum that release Ca 2þ into the cytoplasm in response to different stimuli in many cell types, including oocytes [25,53].…”
Section: Discussionmentioning
confidence: 99%
“…Other known caffeine mechanisms of action include a competitive antagonism of adenosine effects via adenosine receptors (A 1 , A 2A , and A 2B ) [24], inositol triphosphate receptor one antagonism [25] and ryanodine receptor activation [26]. In oocytes, caffeine raises intracellular cAMP levels, and thereby increases cAMP-dependent protein kinase activity, which in turn inhibits meiotic resumption [21,27].…”
Section: Introductionmentioning
confidence: 99%